2003
DOI: 10.1258/135581903322405162
|View full text |Cite
|
Sign up to set email alerts
|

Creating a new articulation between research and practice through policy? The views and experiences of researchers and practitioners

Abstract: Collaborative research within health care organizations succeeded in fostering the implementation of new modes of knowledge production and intervention. Nevertheless, special attention needs to be given to the development of strategies to reduce the discrepancies between values and practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 7 publications
1
44
1
Order By: Relevance
“…43 Academic and professional collaborations are discussed in terms of increasing research productivity and quality, 49 improving learning 32 and enhancing the development of new skills across partnerships. 33 Organisational collaboration is described as reaching outcomes or goals. 34 The literature reviewed in the background search describes outcomes or impacts of collaboration as, for example, the dissemination and implementation of guidelines; 50 improving aspects of services and affecting health outcomes or public health; [51][52][53] promoting successful change; and closing the gap between potential and actual performance.…”
Section: Defining Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Academic and professional collaborations are discussed in terms of increasing research productivity and quality, 49 improving learning 32 and enhancing the development of new skills across partnerships. 33 Organisational collaboration is described as reaching outcomes or goals. 34 The literature reviewed in the background search describes outcomes or impacts of collaboration as, for example, the dissemination and implementation of guidelines; 50 improving aspects of services and affecting health outcomes or public health; [51][52][53] promoting successful change; and closing the gap between potential and actual performance.…”
Section: Defining Collaborationmentioning
confidence: 99%
“…31 Moreover, the outcomes that are supposedly linked to collaboration are often described in abstract terms, for example related to the learning that occurs as a result of the collaboration, 32 or to the development of new skills across partnerships. 33 However, whether or not and how collaboration promotes the implementation of knowledge by end-users is unclear. As this was the 'theory' in the heads of those who established and funded CLAHRCs, we undertook a rapid realist review to identify whether or not this theory is supported by evidence and, if so, why and how collaboration might prompt implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Each needs time and genuine resource commitments from all involved in order to succeed. 81 Participatory approaches aim to enhance both the credibility and ownership of research, addressing barriers that inhibit utilisation and allowing each party to develop a greater understanding of each other's world. 32,39,[82][83][84] To understand the aspirations for cocreated research, we need to refer to Van Collaborative research can enable greater insight into the interpretation of data 3,4,[82][83][84][85][86] by adding a contextual perspective to findings, 85 supporting implementation 14 and enabling the development of more focused real-world RQs.…”
Section: Exchanging Knowledge Relational Approaches and Complexitymentioning
confidence: 99%
“…In our study (and our data which is based solely on one commissioning site), research utilisation was made more difficult to achieve across the purchaser-provider split because it reduced the opportunities for interaction on which evidence flow largely depends. 17,19,21,30,[50][51][52]55,69,74,75,77,[81][82][83][84][85][86][90][91][92] The non-engagement of all stakeholders removed the opportunity to 'achieve stability by consensual adjustment of competing perspectives'. 221 However, in practice there are different models of commissioning 225,227 and the same may not hold true for all of them.…”
Section: Researching the Elusive Nature Of Commissioningmentioning
confidence: 99%
“…Indeed, a systematic review of policymaker's use of research identified two-way communication as the most important facilitator of research (Innvaer et al, 2002). Not only can interaction be used to exchange knowledge about professional norms and expectations (Denis et al, 2003), interactions can help users understand research findings. Early interactions can make the research more responsive to policy-maker needs through the refinement of research questions or contextualization of findings to local needs.…”
Section: The Use Of Research In Policy-makingmentioning
confidence: 99%